2014
DOI: 10.1002/jbm.a.35382
|View full text |Cite
|
Sign up to set email alerts
|

In vivodegradation effects of alloy MgNd2 in contact with mucous tissue

Abstract: Magnesium alloys are currently being investigated for use as resorbable biomaterials. Various applications for magnesium based implant materials have already been presented. Currently, stents and structures that sustain diseased or narrowed vessels seem to be the most promising areas. This study focuses on the use of a magnesium fluoride (MgF2 ) coated magnesium neodymium based alloy (MgNd2 ) and its use as a postsurgery stent material to avoid proliferation in the sinus region. Simple cylindrical shaped speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
3
7
0
1
Order By: Relevance
“…While common alloying elements like Zn and Al form phases with significantly nobler corrosion potentials (Mg 2 Al 3 : −1.01 V SCE ; MgZn 2 : −1.03 V SCE), Mg 3 Nd's corrosion potential is close to the Mg matrix's potential of −1.65 V SCE minimizing the adverse effect of microgalvanic coupling between matrix and precipitate. As shown by Seitz et al the majority of MgNd precipitates seem to distribute along grain boundaries which could result in a slower corrosion due to a barrier effect as described by Song et al Micrographs of alloy Mg‐2Nd have shown no preferential corrosion of grain boundaries or grains within a period of 180 days postsurgery into the sinus region of pigs . Within the same study, the in vivo corrosion rate of Mg‐2Nd was determined to be below 0.02 mg(cm 2 h −1 ) −1 …”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…While common alloying elements like Zn and Al form phases with significantly nobler corrosion potentials (Mg 2 Al 3 : −1.01 V SCE ; MgZn 2 : −1.03 V SCE), Mg 3 Nd's corrosion potential is close to the Mg matrix's potential of −1.65 V SCE minimizing the adverse effect of microgalvanic coupling between matrix and precipitate. As shown by Seitz et al the majority of MgNd precipitates seem to distribute along grain boundaries which could result in a slower corrosion due to a barrier effect as described by Song et al Micrographs of alloy Mg‐2Nd have shown no preferential corrosion of grain boundaries or grains within a period of 180 days postsurgery into the sinus region of pigs . Within the same study, the in vivo corrosion rate of Mg‐2Nd was determined to be below 0.02 mg(cm 2 h −1 ) −1 …”
Section: Introductionmentioning
confidence: 66%
“…Regarding its biocompatibility, alloy MgNd2 was successfully tested in contact with nasal mucosa in an animal study . Moreover, it showed suitable corrosion pattern in contact with nasal mucosa …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allerdings zeigten sich histologisch an der Kontaktfläche zur Schleimhaut sowohl der Stirnhöhle als auch des Recessus frontalis reaktive Gewebe-Hyperplasien und Fibrosen, die als unerwünscht einzuordnen waren. Die schrittweise Degradation des Stents war auch nach 180 Tagen noch nicht abgeschlossen [56][57][58][59]. Fragen zur lokalen und systemischen Toxizität scheinen bisher nicht ausreichend beantwortet zu sein.…”
Section: Magnesium-stentunclassified